Risk Based Technologies - Varde, Prabhakar V.; Prakash, Raghu V.; Joshi, Narendra S. (Springer Nature Singapore : Imprint: Springer, 2019)
This book presents selected topics in implementing a risk-based approach for complex engineering systems in general, and nuclear plants in particular. It addresses gap areas in implementing the risk-based approach to design, operation and regulation, covering materials reliability, digital system reliability, software reliability, human factor considerations, condition monitoring and prognosis, structural aspects in risk-based design as well as the application aspects like asset management for first-of-their-kind projects, strategic management and other academic aspect. Chapters are authored by renowned experts who address some of the identified challenges in implementation of risk-based approach in a clear and cogent manner, using illustrations, tables and photographs for ease of communication. This book will prove useful to researchers, professionals, and students alike.